Preferensi Masyarakat terhadap Ruang Kota sebagai Tempat Relaksasi - Mutia Ayu Cahyaningtyas; Hanson E Kusuma (RUAS (Review of Urbanism and Architectural Studies), 2020)
People who live in urban areas tend to have a higher stress level than those who live in rural areas. Level of stress can be prevented and diminished through the establishment of urban relaxation spaces within the city. Urban city planning needs to consider citizens’ preferences as potential users to obtain the maximum result. This study aims to determine the characteristics of preferred urban relaxation spaces within the city. The research was conducted through a grounded theory approach and exploratory qualitative method. Data collection was carried out based on the open-ended online survey questionnaire with a non-random sampling technique. Data was then analyzed by content analysis in three stages: open coding, axial coding, and selective coding. The finding shows that there are six aspects of preferred urban relaxation spaces: the sense of nature, facilities, tranquility, ambience, accessibility, and quality of space. Research is expected to explore new potentials in urban planning in accordance with the characteristics of its citizens.